Impact of the COVID-19 Pandemic on Sedentary Time and Behaviour in Children and Adults: A Systematic Review and Meta-Analysis - Adam Runacres (MDPI AG, 2021)
The aim of this meta-analysis was to quantify the change in sedentary time during the COVID-19 pandemic and its effect on health outcomes in the general population. One thousand six hundred and one articles published after 2019 were retrieved from five databases, of which 64 and 40 were included in the systematic review and meta-analysis, respectively. Studies were grouped according to population: children (<18 years), adults (18–64 years) and older adults (>65 years). Average sedentary time was calculated, with sub-analyses performed by country, behaviour type and health outcomes. Children were most affected, increasing their sedentary time by 159.5 ± 142.6 min day−1, followed by adults (+126.9 ± 42.2 min day−1) and older adults (+46.9 ± 22.0 min day−1). There were no sex differences in any age group. Screen time was the only consistently measured behaviour and accounted for 46.8% and 57.2% of total sedentary time in children and adults, respectively. Increases in sedentary time were negatively correlated with global mental health, depression, anxiety and quality of life, irrespective of age. Whilst lockdown negatively affected all age groups, children were more negatively affected than adults or older adults, highlighting this population as a key intervention target. As lockdowns ease worldwide, strategies should be employed to reduce time spent sedentary. Trial registration: PROSPERO (CRD42020208909).